Experion: A framework for contextualizing evidence in expert finding - Gonçalves, Rodrigo; Dorneles, Carina F. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2021: Anais Estendidos do XXXVI Simpósio Brasileiro de Bancos de Dados, 2021)
Expert finding is traditionally related to a subject of research in information retrieval and, often, is taken to mean "expertise retrieval within a specific organization". The task involves finding an expert in an expertise topic. Even though there are interesting proposals in the literature, they do not consider the context in which a given expertise is bound. This Ph.D. thesis introduces the concept of a framework that chronologically contextualizes search results in expert finding. Our motivation is to provide more accurate results of search processes related to finding experts in a given topic, contextualizing the expertise on professional/academic activities, an open research topic. In this paper, we present the main concepts of the framework we are developing and a general overview of its operation. At the moment, we are using the Lattes platform as a data source, for which we developed a process to extract expertise evidence, supported by the Crossref database.